Satisfaction with health care services in young people with cerebral palsy in the transition period: results from a European multicenter study - Muehlan, Holger; Alvarelhao, Joaquim; Arnaud, Catherine; Cytera, Chirine; Fauconnier, Jerome; Himmelmann, Kate; Marcelli, Marco; Markwart, Henriette; Rapp, Marion; Schmidt, Silke; Thyen, Ute (Frontiers in Medicine, 2024)
Background Young people with chronic health conditions and disabilities rely on the healthcare system to maintain their best possible health. The appropriate delivery and utilization of healthcare services are key to improve their autonomy, self-efficacy and employment outcomes. The research question of our study is directed toward investigating if poor availability and accessibility of healthcare services in general, as identified by unmet needs in healthcare, are associated with dissatisfaction with healthcare. Methods Within a European multicenter observational study, 357 young adults with cerebral palsy aged 19–28 were included. We assessed special healthcare needs, utilization of healthcare services, and satisfaction with healthcare applying the short-form of the YHC-SUN-SF, environmental and social variables (EAEQ) as well as indicators for severity of condition and functionality (e.g., GMFCS) of these participants based on a self-, assisted self- or proxy-reports. We used correlation analyses to explore associations between satisfaction with healthcare and respective indicators related to availability and accessibility of healthcare services as well as severity of the condition. In addition, we included reference values for satisfaction with heath care from young adults with various chronic conditions assessed within population-based surveys from some of the European countries included in the study. Results We identified several unmet healthcare needs, especially for widely used and established services (e.g., physical therapy). Satisfaction with healthcare (YHC-SUN-SF general and subscale scores) was moderate to high and almost consistently better for the sample of young adults with cerebral palsy as compared to reference values for young adults with various chronic conditions assessed within general population surveys). Correlation coefficients between satisfaction with healthcare and utilization of services and (unmet) healthcare needs were low, also with different indicators for severity of the condition or functionality. Conclusion Young adults with cerebral palsy reports of unmet healthcare needs varied largely but showed substantial deficits in some aspects. This seems to have no impact on the satisfaction with healthcare those patients currently receive. We conclude that these are two different constructs and somewhat independent indicators to evaluate the quality of healthcare. Clinicians and other practitioners should consider this distinction when monitoring patient needs in their daily practice.